Palafitas serão apartamentos: concepções, mecanismos e limites da participação popular no PAC Rio Anil no bairro da Liberdade, em São Luís do Maranhão - Pinheiro, Sílvio Sérgio Ferreira (2013)
The purpose of this study is to discuss the character of popular participation on the Rio Anil PAC Project, at Liberdade neighborhood, in São Luis, capital of Maranhão State. The Growth Acceleration Program (PAC) was launched in Brazil during the second term of Luiz Inácio Lula da Silva s presidency, on January 22, 2007, and in São Luis during Jackson Lago s term, on May 27, 2008. The Rio Anil Project was a result of the partnership between the Federal Government, by the Ministry of Cities and the Special Secretary of Policies for the Racial Equalty Promotion (SEPPIR), and the Maranhão State Government (2007-2009 term), mainly by the State Secretaries of Cities and of Racial Equalty. The semantic fieldin which the debate is developed largely includes expressions such as popular participation , democracy , housing and city . During the methodological process, data and primary information were collected through qualitative interviews with people living in palafitas(kind of a precarious block house made of wood over the river bank), leaders, public administrators and technicals, as well as secondary information were found on official documents and reports from Federal and State Governments, besides press reports (local and regional newspapers, magazines and blogs). In addition, some resources from the militancy observation were used, when there was participation in events and meetings at Liberdade neighborhood or with public agencies and the community